Assessment of knowledge, attitude and practices concerning food safety among restaurant workers in Putrajaya, Malaysia - Ab. Hamid, Rosnani; Radu, Son; Othman, Mohhidin; Toh, Poh See; Chai, Lay Ching (International Institute for Science, Technology & Education, 2014)
The aim of this study is to evaluate the knowledge, attitudes and practices on food safety held by food handlers working in restaurants in Putrajaya, Malaysia. Inappropriate food handling is the main factor contributing to food borne disease outbreaks. A total of 127 food handlers were randomly selected from 23 restaurants and the data collected in September 2013 through self-administered questionnaires were analyzed using the SPSS version 16. Generally knowledge of food safety was good with the mean score 90.3 ± 7.787. However, respondents lacked knowledge about the hazards of reheating cooked food (75.1 ± 25.662) and the safe temperature of cooked food (71.9 ± 33.548). Knowledge differed significantly by age groups (F=2.530; p=0.044). Respondents had positive attitudes about food safety, with a mean score of 93.9 ± 6.813, although there were significant differences between trained and untrained workers (t=2.406; p=0.018); Malaysian ethnic groups (F=2.502; p=0.034); Malaysians and non-Malaysians (t=3.273; p=0.001) and due to differences in education levels (F=6.057; p=0.003). The mean score for practice was 92.9 ± 7.647 and again there were significant differences related to education levels (F=1.345; p=0.003), gender (t=-2.120; p=0.036) and ethnicity of Malaysian workers (F=2.502; p=0.034). A strong relationship was found between knowledge and attitudes about food safety (r=0.266; p=0.002) and between knowledge and practice (r=0.203; p=0.022). In conclusion, this study suggests that food handlers in Putrajaya restaurants displayed good knowledge, a positive attitude and an excellent practices regarding food safety. Yet results showed the food workers still lack basic knowledge of food safety, particularly related to reheated food and safe temperatures for cooked food.